2023
DOI: 10.3390/nu15020455
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nerolidol Renal Dysfunction following Ischemia–Reperfusion Injury in the Rat

Abstract: Efforts to decrease the deleterious effects of renal ischemia–reperfusion injury (IRI) are ongoing. Recently, there has been increasing interest in using natural phytochemical compounds as alternative remedies in several diseases. Nerolidol is a natural product extracted from plants with floral odors and has been proven to be effective for the treatment of some conditions. We investigated the effect of nerolidol in a rat model of renal IRI. Nerolidol was dissolved in a vehicle and administered orally as single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…[37]. Moreover, one study involving renal IRI in rat models also revealed a significant elevation of IL-1β levels in kidney tissues after ischemia [39][40][41].…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…[37]. Moreover, one study involving renal IRI in rat models also revealed a significant elevation of IL-1β levels in kidney tissues after ischemia [39][40][41].…”
Section: Histopathological Examinationmentioning
confidence: 99%